2010
DOI: 10.1093/hmg/ddq315
|View full text |Cite
|
Sign up to set email alerts
|

α-Cardiac myosin heavy chain (MYH6) mutations affecting myofibril formation are associated with congenital heart defects

Abstract: Congenital heart defects (CHD) are collectively the most common form of congenital malformation. Studies of human cases and animal models have revealed that mutations in several genes are responsible for both familial and sporadic forms of CHD. We have previously shown that a mutation in MYH6 can cause an autosomal dominant form of atrial septal defect (ASD), whereas others have identified mutations of the same gene in patients with hypertrophic and dilated cardiomyopathy. In the present study, we report a mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 46 publications
2
118
0
4
Order By: Relevance
“…Mutations in genes encoding sarcomere proteins have been identified in a significant proportion of LVNC patients, 1,2 as well as in association with congenital heart defects (CHDs). [3][4][5] The presence of sarcomere mutations suggest an underlying cohesiveness of cardiomyopathy and structural CHDs, supporting the essential role for normal sarcomere function during cardiac development. In this issue of Circulation Cardiovascular Genetics, 2 papers 6,7 report on the results of whole exome sequencing and whole genome sequencing (WGS) in patients with LVNC and HLH, respectively.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Mutations in genes encoding sarcomere proteins have been identified in a significant proportion of LVNC patients, 1,2 as well as in association with congenital heart defects (CHDs). [3][4][5] The presence of sarcomere mutations suggest an underlying cohesiveness of cardiomyopathy and structural CHDs, supporting the essential role for normal sarcomere function during cardiac development. In this issue of Circulation Cardiovascular Genetics, 2 papers 6,7 report on the results of whole exome sequencing and whole genome sequencing (WGS) in patients with LVNC and HLH, respectively.…”
mentioning
confidence: 88%
“…[3][4][5] Dominant heterozygous MYH6 mutations with variable penetrance were described in atrial septal defect and other CHD. In addition, other rare heterozygous MYH6 variants were identified in dilated and hypertrophic cardiomyopathy.…”
Section: Hypoplastic Left Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Als wichtigste Vertreter dieser Gruppe sind hier MYH6, MYH7, MYH11 (kardiale Muskelbestandteile) und ACTC1 (kardiales Aktin) zu nennen, die insbesondere bei der EbsteinAnomalie [20], ASD [21] oder anderen Herzfehlbildungen [22] gefunden werden können. Vor allem die kardialen Strukturproteine zeigen eine große Überlappung mit den Kardiomyopathien.…”
Section: Nicht-syndromale Strukturelle Herzfehlerunclassified
“…We 21,[23][24][25] and others 22,26 have shown that in humans, mutations of genes encoding contractile proteins expressed in the developing heart and great vessels can cause a wide spectrum of CHD (Table). Mutations of the ␣-cardiac actin (ACTC1) 21 and ␣-cardiac myosin heavy chain (MYH6) [23][24][25] genes have been found in families with autosomal dominant forms of atrial septal defect and in sporadic cases of other cardiac malformation.…”
Section: Mutations Affecting Contractile Proteins Cause Heart Malformmentioning
confidence: 99%